Analysis of 1 Timothy 3:1-7 and its Implications for the Personality Competence of Sunday School Teachers in Indonesia - I Putu Ayub Darmawan; John Mardin; Martinah Martinah; Maria Lidya Wenas (Sekolah Tinggi Teologi ATI Anjungan Pontianak, 2023)
Christianity in Indonesia can continue to thrive and grow as the church is constantly regenerating, a process that began with Sunday School. Sunday School is the church's primary means of educating the next generation of the church knowledge about Christ. However, there are still Sunday school teachers who do not take the significance of their position seriously. This cannot be separate from the lack of personality competence of Sunday school teachers; consequently, Sunday school teachers in Indonesia frequently disregard their personality competence. The significance of the personality competence of Sunday School teachers cannot be overstated. In 1 Timothy 3:1-7, it is elucidated that an elder who serves as a teacher must possess a personality that aligns with the requisite qualities of an elder. In this section, the writer performs a biblical analysis of 1 Timothy 3:1-7, identifying two distinct frameworks that outline the necessary competencies of an elder's personality. The aforementioned personality competencies encompass possessing a favourable disposition in one's surroundings as well as exhibiting a spiritually healthy personality. The personality competencies outlined have implications for Sunday school teachers in Indonesia. Specifically, it is recommended that Sunday school teachers possess a personality that aligns with both social norms and Christian values.